Perancangan Antarmuka Pengguna Sistem Pengelolaan Hasil Penilaian Siswa menggunakan Human Centered Design (Studi Kasus : SMKN 2 Bojonegoro) - Andini Ayu Larasati; Hanifah Muslimah Az-Zahra; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The research about system that is used for managing student score was based on the school that is the research object condition which does not have a system that can help the teacher to easily manage their student score. therefore, Microsoft Office Excel and Google Form was used to manage the student's result score on their study. The research object consist of 10 major which have three grades, therefore making the management of the score inefficient both in time and energy and making in less effective. Another problem of using those method is that there is a high possibility of losing data. based on that problem, the researcher is designing a interface for information system that will be used for managing the student's score using a Human Centered Design (HCD) method. the method is used for designing a interface that will focus on the user needs that will make ease on the system usability. the research will resulting a high fideality prototype used by 1 user (vice principal on curriculum field) and 3 user groups (homeroom teacher, subject teacher, and extracurriculer builder). The last testing method useed will be using a usability testing method with System Usability Scale (SUS) for the assessment. System Usability Scale questionnaire will be used for calculate usability level based on the user point of view. the end result of System Usability Scale will obtain summary of all user total score which is 72. the score result will then show the interface design is accepted by the user candidate.